Response of Class VI Students of SD Negeri 040538 Sampun to Mathematics Lessons Concerning Space-Constructing Nets - Zein, Alfajra Muliaty Puteri; Sembiring, Nanda Br; Kandi, Tri Dina; Simatupang, Yangel Ruth Anastasia (Journal of Educational Analytics, 2024)
The purpose of this research is to determine student responses and teacher potential in implementing mathematics learning, namely in selecting teaching materials, methods and techniques for delivering the material. The method used is a quantitative method in the form of data collection based on the results of a questionnaire filled in directly by the respondent. Data collection techniques result from teacher and student observations as well as evaluation of learning processes and outcomes. The sample in this study was 25 class IV students at SD Negeri 040538 Sampun District. Dolat Rayat, Kab. Karo. The research results showed that students' response activities to the material were very good. In conclusion, learning resources are resources that can be utilized in learning activities. The teacher's role in providing learning resources is very important so that the learning process can run smoothly and be achieved well. Meanwhile, in the research conducted by the author, it was found that it is true that the skills of the teachers at the elementary school and also the way students learn to take part in the Mathematics lessons given by the teacher are in the good category and are implemented well at the elementary school.